KONFLIK ANTARA KEDAULATAN NEGARA DAN HAK ASASI MANUSIA DALAM PERSPECTIVE HUKUM PERDATA: SUATU PENDEKATAN YURIDIS NORMATIF DAN ANALISIS TEORI HUKUM - Ernawati; El Walad, Amin (Rechtsregel : Jurnal Ilmu Hukum, 2025)
This article examines in depth the conflict between the principles of state sovereignty (nation rights) and human rights within the framework of civil law, using normative juridical methods. The research focuses on the dynamics that arise when civil disputes involve foreign parties or transnational contracts, which demand a balance between national jurisdiction and universal human rights principles. Through a review of legal theories such as legal positivism, natural law, subjective rights theory, and justice theory, this article analyzes how the principle of sovereignty applied absolutely can potentially weaken the protection of individual civil rights, particularly in the context of legal globalization. The main findings indicate that a legalistic approach that overemphasizes the supremacy of national law is often inadequate to address the complexity of cross-border civil issues. The tension between sovereignty and the universality of human rights becomes increasingly apparent when states use the pretext of sovereignty to limit the recognition or implementation of the rights of foreign individuals within the domestic legal system. This raises fundamental questions about the limits of state legitimacy in addressing transnational demands for justice. This article recommends the need to reconstruct the national civil law approach to be more responsive to developments in human rights at the international level. Integrating substantive justice values into the formation and interpretation of civil law norms is considered crucial to ensure that the state not only exercises formal legal authority but also fulfills its moral and legal responsibilities in guaranteeing the protection of individual rights, regardless of citizenship or legal status.